"Help, I'm Getting Bullied": Examining Sequences of Teacher Support Messages Provided to Bullied Students. Issue 1 (1st January 2019) - Danielson, Carly M.; Jones, Susanne M.
Abstract : Many students who seek out teachers for help when getting bullied report receiving unhelpful support. We theorized that the placement of support types (emotional, informational, network) in a conversation influences participants' ( N  = 640) supportiveness evaluations. Results suggest that 1) conversations with more than one support type were evaluated as most supportive; 2) conversations featuring network support anywhere were viewed as more supportive; and 3) the emotional support–only conversation was viewed as least supportive, whereas the emotional-and-network support conversation was viewed as most supportive. We end by providing useful information for bullied students' postbullying adjustments and bullying education curricula for teachers.